The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pone.0282049
|View full text |Cite
|
Sign up to set email alerts
|

Living experiences of people living with HIV-AIDS from the client’s perspective in nurse-client interaction in Indonesia: A qualitative study

Abstract: Background Nurse–client interaction when providing nursing services is limited to optimizing treatment and self-care, with limited focus on the psychological problems of people living with HIV-AIDS. However, psychological problems manifest more often than the health risks of the disease itself. This study aimed to determine the emotional response of people living with HIV-AIDS who received limited attention from nurses from the perspective of nurse–client relationship. Patients and methods A phenomenological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Decreased physical condition, high threat of death, coupled with discrimination or bad stigma addressed to PLHIV that causes their high psychological disorders that can cause a decrease in the quality of life of PLHIV (Girianto & Wiwik, 2017). Research conducted by Nasir et al (2023) found the same thing about the poor quality of life of PLHIV with depression due to discrimination and/or bad stigma in the PLHIV environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased physical condition, high threat of death, coupled with discrimination or bad stigma addressed to PLHIV that causes their high psychological disorders that can cause a decrease in the quality of life of PLHIV (Girianto & Wiwik, 2017). Research conducted by Nasir et al (2023) found the same thing about the poor quality of life of PLHIV with depression due to discrimination and/or bad stigma in the PLHIV environment.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that the problem of accepting HIV status in the form of rejection of HIV status experienced by PLHIV greatly affects their social life. Self-acceptance of HIV status has a (Maxwell Landri Vers Malakauseya, et al) positive impact on PLHIV (Nasir et al, 2023). Accepting HIV status encourages a person to seek health care and is often accompanied by a sense of need and value for HIV medical care (Horter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with HIV often face stigma and discrimination, particularly within their local communities (Greenwood et al, 2022 ). Experiencing such stigma and discrimination can cause significant psychological issues for those living with HIV/AIDS, including increased anxiety, depression, and heightened risk of suicidal thoughts or actions (Nasir et al, 2023 ). Individuals with HIV often live with fear related to family, society, and religion (Parsons, 2022 ).…”
Section: Introductionmentioning
confidence: 99%